Agrochemical innovation for crop health: moving forward through dynamic disorder - Hsiao, An-Shan (Frontiers in Plant Science, 2026)
Global climate change has huge negative impacts on crop health. Strategies for increasing crop yield and resistance to biotic and abiotic stress factors (pathogenic microbes, insect pests, drought and heat waves, flooding etc.) are important to achieve sustainable agriculture for food security. Breeding for elite crop varieties takes time and may face challenges in commercialization. Besides the development of genetic tools to generate climate-smart crops, recent innovations in agrochemicals as interventions for improving crop health are emerging. This article discusses the current advances in three small technologies, RNAs, peptides and nanotechnology, in targeting plant diseases and improving productivity as well as in future research directions for agrochemical innovation. Although previously assumed as undruggable in human diseases, protein disorder has unique conformational features and plays critical roles in regulating various biological processes controlling crop productivity and stress resistance in planta. The article proposes the potential incorporation of protein disorder in these three approaches and intelligent agrochemical innovation with tailored functionalities.